Application of direct fluorescence-based live/dead staining for assessment of antifungal activity of coconut oil against candida albicans - Mukhtar, Nor Izzah; Abllah, Zurainie; M., Azrul Naim; Shahdan, Intan Azura; Long, Kamariah; Haron, Ummi Aqilah (2019)
Candida albicans is one of the common causes for oral candidiasis worldwide. The proliferation of antifungal-resistant C. albicans has become a major concern. This study was carried out to evaluate activated virgin coconut oil (AVCO) and crude extract of virgin coconut oil (VCO) as new antifungal agents for treatment of oral candidiasis. C. albicans viability was determined using LIVE/DEAD bacterial viability kit. C. albicans cells were grown in yeast peptone dextrose (YPD) broth overnight. The fungus was treated with AVCO and VCO at the concentration of minimum fungicidal concentration (MFC) of 6.24 mg/mL and incubated for three different time points (1, 2, and 3 h). To evaluate the viability of C. albicans, SYTO 9 and propidium iodide (PI) staining were used and the cells were observed using fluorescence microscopy. C. albicans treated with AVCO showed more dead cells compared to cells treated with VCO. The data indicate that exposure of C. albicans to AVCO was the most inhibitory to its growth (p < 0.01).